Assessing network authorization policies via reachability analysis. (November 2017) - Basile, Cataldo; Canavese, Daniele; Pitscheider, Christian; Lioy, Antonio; Valenza, Fulvio
Abstract: Evaluating if a computer network only permits allowed business operations without transmitting unwanted or malicious traffic is a crucial security task. Reachability analysis – the process that evaluates allowed communications – is a tool useful not only to discover security issues but also to identify network misconfigurations. This paper presents a novel approach to quantify network reachability based on the concept of equivalent firewall – a fictitious device, ideally connected directly to the communicating peers and whose policy summarizes the network behaviour between them – that can be queried to derive reachability information. We build equivalent firewalls by using a mathematical model that supports a large variety of network security controls (like NAT, NAPT, tunnels and filters up to the application layer) and allows an accurate analysis. The presented approach is efficient and highly scalable, as confirmed by tests with a large corporate network as well as synthetic networks.